Kontribusi keberfungsian keluarga terhadap kesejahteraan subjektif pada remaja etnis Minang - Jihan Nabilah CS; Tesi Hermaleni (Jurnal Ilmiah Psikologi Terapan, 2021)
The studies show that culture and family functioning have a contribution to the well-being of youth. Ethnic Minang with matrilinear culture and collective owned, of course, also plays a role in teenagers’ lives. Researchers aim to test the role of a family’s functioning towards adolescents’ subjective well-being in the Minang ethnicity. The design of this study is quantitative with the selection of samples in the form of purposive sampling. Participants in the study were 315 ethnic Minang adolescents who had filled out questionnaires containing Family Assessment Device and subjective well-being scales. A simple linear regression analysis test shows that family functioning contributes to subjective well-being in ethnic Minang youth (R2 = 0.177, F=67.347, p=0.000). That is, family functioning as a predictor variable contributed 17.7% to subjective well-being. The more optimal the functioning of a family, the more its members feel prosperous.